Sikap Guru terhadap Hasil Belajar Siswa Berkesulitan Belajar di Sekolah Dasar Penyelenggara Pendidikan Inklusif - Kusumastuti, Grahita; Marlina, Marlina; Efendi, Jon; Sumekar, Ganda; Armaini, Armaini; Hendrawati, Tika (Jurnal Pendidikan Kebutuhan Khusus, 2018)
This study aims to determine the teachers’ attitude toward performance of students with learning disabilities in t inclusive school. This research used deskriptive quantitative approach. The instrument used was attitude instrument that was given to 54 students with learning disabilities in Padang. Data collected were analyzed quantitatively and described. The results of data found that teachers’ attitude which measured in three aspects have score 77.93% in understanding the learning result of students with learning disabilities. In affective aspect, teachers’ attitude have scores 80.50% in accepting the learning result of students with learning disabilities. Whereas in conative aspects, teachers’ attitude have score 77.92% in behave towards the learning result of students with learning disabilities.